Faktor-Faktor yang Mempengaruhi Produktivitas Karyawan Pada CV Timur Jaya Pekanbaru - Astri Ayu Purwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Human resource management aims to utilize, develop, research, human resources and existing natural resources so that they can be managed effectively and efficiently. This study aims to obtain empirical evidence about the effect of Motivation, Participatory Leadership, and Work Safety on employee Productivity at CV Timur Jaya Pekanbaru. The method used is multiple linear regression analysis. with a sample of 43 respondents from CV Timur Jaya Pekanbaru employees. From the results of the study, it was shown that Motivation had a positive and significant effect on employee productivity, while Participatory Leadership and Work Safety did not significantly influence employee productivity at CV Timur Jaya Pekanbaru. Keywords : Motivation, Parcipatory Leadership, Work Safety, amd Productivity